(untitled) (Technological Innovations Journal, 2024)
The objective of this article is to present an exhaustive review on the use of flight simulators for the training of aviation maintenance technicians in Bolivia, providing an overview of their effectiveness and practical applications. A qualitative, documentary-type approach was followed. Documentation on the evolution of technology in aviation and the technological situation of aeronautics in Bolivia was reviewed, where it is pointed out that flight simulators are a valuable tool for the training of aeronautical maintenance technicians in the country, the different types of flight simulators currently available and their effectiveness for the training of maintenance technicians is analyzed, concluding that simulators are an essential tool in the training of maintenance technicians in aviation, the current training of maintenance technicians in aviation is discussed. Bolivia and the UMSA aeronautics career stands out as an important option for the training of highly trained technicians.